Thailand : Wanted, A Quality Education for All - World Bank Group (Bangkok, 2015)
Over the past two and a half decades, Thailand has made great progress in expanding basic education, closing the gap in attendance between socioeconomic groups, and putting more focus on the quality of education. Building on this progress, it appears that even more can be done to maximize the potential of Thailand’s students to become productive workforce participants. Functional illiteracy can be seen across the various types of schools in Thailand, indicating that there are still system-wide issues affecting the quality of education. Improving educational outcomes among these poorer-performing students can have major impacts at the individual level and for Thailand’s economic growth prospects. Having a workforce with stronger analytical reasoning and problem solving skills - skills that extend well beyond simply being functionally literate - can help Thailand move up the value-added ladder to a more knowledge-based economy. Therefore, addressing the remaining gaps will enable Thailand to improve its competitiveness, economic growth, and prosperity.